Analisis Kesesuaian Kurikulum DPIB SMK dengan Kebutuhan Pasar Kerja: Studi Wawancara dengan Lulusan dan Pengusaha Konstruksi - Abidi, Azidan El; Ichwanto, Muhammad Aris; Sokhe, Akhmad (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to analyze the suitability of the Building Information Modeling Design (BID) curriculum in Vocational High Schools (SMK) with the real needs in the job market, especially in the construction industry. Qualitative research methods were used through in-depth interviews with three groups of respondents: BID teachers, graduates working in the construction industry, and construction entrepreneurs. The results of the study indicate that the BID curriculum has provided a strong foundation for students, with basic competencies such as reading engineering drawings and project management. However, there are shortcomings in mastering the latest technology and developing soft skills. Graduates are often less prepared to face the demands of the industry that increasingly prioritize technology and collaboration. The existing Prakerin program also needs to be adjusted to be more relevant to industry needs. This study suggests the need for integration of modern technology in the curriculum, increased focus on soft skills, and further involvement in the Prakerin program to improve graduates' work readiness. Synergy between the world of education and industry is essential to ensure that graduates can contribute significantly to the competitive construction job market.